The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1002/app.34257
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical immobilization of ascorbate oxidase in poly(3,4‐ethylenedioxythiophene)/multiwalled carbon nanotubes composite films

Abstract: Immobilization of ascorbate oxidase (AO) in poly(3,4-ethylenedioxythiophene) (PEDOT)/multiwalled carbon nanotubes (MWCNTs) composite films was achieved by one-step electrochemical polymerization. The PEDOT/ MWCNTs/AO modified electrode was fabricated by the entrapment of enzyme in conducting matrices during electrochemical polymerization. The PEDOT/MWCNTs modified electrodes were investigated by cyclic voltammetry and electrochemical impedance spectroscopy. The experimental results showed that the composite fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 54 publications
2
10
0
Order By: Relevance
“…Similar results have been reported for catalase covalently bound to electrospun nanofiber meshes filled with carbon nanotubes [40]. It was also reported that the conducting carbon nanotubes were able to promote direct electron transport from redox enzymes such as ascorbate oxidase, peroxidase, and Lac [38,[40][41][42][43][44][45][46]. Therefore, PpPD/Fe3O4 nanocomposite may also be suitable for enzyme immobilization, especially for redox enzymes.…”
Section: Removal Of Rb-19supporting
confidence: 80%
“…Similar results have been reported for catalase covalently bound to electrospun nanofiber meshes filled with carbon nanotubes [40]. It was also reported that the conducting carbon nanotubes were able to promote direct electron transport from redox enzymes such as ascorbate oxidase, peroxidase, and Lac [38,[40][41][42][43][44][45][46]. Therefore, PpPD/Fe3O4 nanocomposite may also be suitable for enzyme immobilization, especially for redox enzymes.…”
Section: Removal Of Rb-19supporting
confidence: 80%
“…where R b is the R ct measured at a bare electrode, R m is the R ct measured at a modified electrode under same conditions [28,42,43]. The value of θ is about 65.64%, which also further confirmed that GOx were covalently immobilized onto the surface of ILs-PEDOTM-MWCNTs-COOH electrode.…”
Section: Electrochemical Impedance Spectroscopysupporting
confidence: 56%
“…The formation of this loop could be explained as the characteristics of nucleation process. As compared with EDOT polymerization, during electropolymerization process, the redox peaks of EDOT‐MeCl appeared at +0.46 V and +0.16 V, which attributed to the p ‐doping/dedoping processes of PEDOT‐MeCl film formed in previous scans. Upon sequential cycles, redox currents increased, implying that the formed electroactive and conductive layer on the gold electrode surface (light‐blue to blue‐black as the deposit thickened) was gradually increasing.…”
Section: Resultsmentioning
confidence: 94%